AN OUTBREAK OF FOOT AND MOUTH DISEASE IN AN ORGANIZED PIG FARM OF ASSAM - BORPUZARI, R.N.; DAS, J.; RAHMAN, M.; HAZARIKA, D.; SAIKIA, M.R. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTIn an outbreak of foot and mouth disease (FMD) in an organized farm, out of 657pigs, 534 (81.28 %) animals were affected and 17 died. The disease was confirmed asFMD by Sandwich ELISA and serotype A of FMD virus was identified. By adopting scientificmanagemental practices mortality rate could be restricted to 2.5 per cent. Of the 17 deadanimals, 15 animals were below 6 months and 2 were above 8 months of age. Higher casefatality was recorded in the young animals which might be due to lack of immunity andmaturity of the immune system. Vaccination of pigs with cattle FMD vaccine was not found tobe useful.Key words: Pig, FMD Outbreak, Organized farm, Mortality and Morbidity.